Financial Resource Allocation and e Commerce Adoption Among SMEs in Kericho County –Kenya - Kiplang’at Bii, John; Cherotich Asiega, Irene (kabarak university, 2016)
Information and Communications Electronic Commerce (e-commerce) wide range of business processes The paper discusses effects aspects such as Government expenditure within the firm, loans and grants on the levels commerce strategies
Keywords: Financial Resource allocation; SME's; E-commerce